Anomalies Associated with Ano Rectal Malformation: Experience in Dhaka Shishu (Children) Hospital (Faridpur Medical College Journal, 2016)
Anorectal Malformation is one of the most common congenital anomalies. It is associated with others anomalies. But those others anomalies are sometime neglected. The purpose of this study is to review the incidence of other congenital anomalies associated with anorectal malformation (ARM). This prospective study was carried out in the department of Pediatric Surgery, Dhaka Shishu (Children) Hospital during the period of June, 2013 to July, 2014. A number of 45 cases were included and data were collected on the type of ARM and associated congenital anomalies which were categorized according to organ system. Total study population was 45. Male: Female ratio was 1.37:1. Majority (55.55%) presented with ARM without fistula, followed by recto vestibular fistula 26.67%, perineal fistula 13.33%, and 2 patients had cloacal anomaly. Thirty two (71.1%) patients had associated congenital anomaly. Among them, 42%, urogenital anomalies, 37.78% cardiovascular, 20% craniofacial anomalies, 11.11% musculoskeletal and anomalies of central nervous system 11%. Among 32 patients, 57.14% patients had multiple congenital anomalies. It is imperative that a thorough clinical evaluation and systemic investigations of all patients with anorectal malformation necessary to exclude or confirm the presence of genitourinary, cardiac and other abnormalities which are directly related with mortality and morbidity.Faridpur Med. Coll. J. Jan 2015;10(1): 23-25